KONTRADIKSI KONSEP KHILAFAH DALAM PERSFEKTIF ULAMA BABEL DAN IMPLIKASINYA TERHADAP UKHWAH ISLAMIYAH DAN UKHUWAH BASYARIYAH DI BANGKA BELITUNG - Suparta, Suparta (Scientia: Jurnal Hasil Penelitian, 2021)
The Khilafah is one of the contradictory concepts not only among Muslim intellectuals but also among scholars. One party is of the opinion that the concept of khilafah is a patent concept that must be implemented by every Muslim if it is not implemented or does not care about the caliphate then it is sinful. On the other hand, there are scholars who argue that the caliphate only exists and can be implemented during the time of the Prophet alone because the only person who deserves to be amiirul mu'miniin is only the messenger of Allah because he is ma'shum. This contradiction is also felt in the area of ​​the Bangka Belitung archipelago, the majority of scholars in Babel (from MUI, NU and Muhammadiyah) they say that if the caliphate is forced into a system of government in Indonesia it cannot because it will result in a split, which has implications for ukhuwah Islamiyah and ukhuwah basyariyah. This is because the Indonesian nation already has its own philosophy, namely Pancasila and already has its own law, namely the 1945 Constitution. In fact, the unity of the Indonesian nation has been bound by the motto Unity in Diversity. Therefore, if the concept of khilafah is enforced as a system of government, especially if you want to replace Pancasila, the majority of the Babylonian Ulama will disagree because it can cause divisions between religious communities, nationals and people of all countries.